Impulsive and hybrid dynamical systems : stability, dissipativity, and control - Haddad, Wassim M., 1961-; Chellaboina, VijaySekhar, 1970-; Nersesov, Sergey G., 1976- (Princeton series in applied mathematics., 2006)
This book develops a general analysis and synthesis framework for impulsive and hybrid dynamical systems. Such a framework is imperative for modern complex engineering systems that involve interacting continuous-time and discrete-time dynamics with multiple modes of operation that place stringent demands on controller design and require implementation of increasing complexity--whether advanced high-performance tactical fighter aircraft and space vehicles, variable-cycle gas turbine engines, or air and ground transportation systems. Impulsive and Hybrid Dynamical Systems goes beyond similar.